Determinants of Link and Match in Vocational High Schools: The Role of Effective Leadership, Curriculum Management, and Teachers’ Professional Competence - Darius Sulivanto, Erik; Nurkolis, Nurkolis; PS, Supriyono (Lembaga Teewan Journal Solutions, 2026)
The successful implementation of the link and match policy in vocational education requires effective leadership, adaptive curriculum management, and teachers' professional competence. However, empirical evidence examining their combined contribution remains limited, particularly in Indonesian vocational high schools. This study analyzed the effects of effective leadership, curriculum management, and teachers' professional competence on the implementation of link and match in public vocational high schools in Grobogan Regency, Indonesia. A quantitative correlational design was employed involving 166 teachers selected through proportional random sampling from three public vocational high schools. Data were collected using validated questionnaires and analyzed using descriptive statistics and multiple linear regression after meeting the assumptions of normality, linearity, multicollinearity, and heteroscedasticity. The results indicated that all three variables had positive and significant effects on link and match implementation. Teachers' professional competence showed the strongest contribution, emphasizing its role in translating curriculum into industry-relevant learning. Collectively, the three variables explained 98.2% of the variance in link and match implementation. These findings highlight the importance of integrating instructional leadership, curriculum management, and continuous teacher professional development to strengthen vocational education quality and better align school outcomes with industry needs.